Strategi Disaster Risk Manajement Pada Bencana Banjir Di Kabupaten Wajo - Rasmiani, Rasmiani; Mappamiring, Mappamiring; Abdi, Abdi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aimed to explain the Disaster Risk Management Strategy to overcome the flood disaster that occurred in Wajo Regency which included environmental scanning, strategy formulation, strategy implementation as well as evaluation and control. The type of research used  qualitative. While the data collection technique used observation, interviews and documentation. There were 5 informants in this study. The results of this study showed that the Disaster Risk Management Strategy for Flood Disaster in Wajo Regency, measured from four indicators, was not optimal, due to various factors such as the increase in the number of areas affected by floods from year to year and inadequated facilities and infrastructure owned by the Agency. Regional Disaster Management of Wajo Regency thus hampering the handling of flood disasters.Keywords: Strategic Management, Disaster Risk, Flood Disaster